Online Nutrition and Menstruation Education: Effects on Eating Habits of Banyumas Junior High Girls - Hapsari, Pramesthi Widya; Surijati, Katri Andini; Prasetyo, Teguh Jati; Khoiriani, Izzati Nur; Proverawati, Atikah (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2025)
Adolescence is a critical developmental phase marked by significant physical, emotional, and social transformations, including the onset of menstruation and the formation of long-term eating habits. This study aimed to evaluate the impact of different online nutrition education on adolescent eating habits. A quasi-experimental study with a pre- and post-test design was conducted over one month, involving 57 participants aged 13 years. Participants were divided into treatment group (n=33), which received education through the Application and a control group (n=24), which received education through WhatsApp. An adolescent eating habits questionnaire was used to assess eating habit during menstruation, and paired t-tests were conducted to analyze changes within each group. The majority of participants in both groups had normal nutritional status (54.5% in the treatment group and 66.7% in the control group). Although no statistically significant difference of eating habit scores was found between the groups, the control group (WhatsApp-based education) showed a trend toward improvement, with a p-value of 0.054. The findings revealed a significant trend towards improving eating habits, especially fruit consumption among participants who received WhatsApp-based education, indicating that modern communication platforms may enhance engagement and promote positive dietary changes in adolescents.